Gender relations and working conditions in the productive sector of organic bananas in Sullana, Piura - Vásquez Zamora, Guiomar (2020)
For the past 19 years, associations of farmers in the province of Sullana have been producing and exporting organic bananas certified by Fair Trade for Europe, Asia and the United States. In this contextual framework, this article analyzes how gender relations, expressed in the sexual division of labor, are changing if the incorporation of women into the salaried employment of organic bananas has generated their empowerment; as well as knowing if working conditions are defined by culture and labor laws. This article presents the results of the Thesis - 2016 - UNMSM, with information updated to 2019, entitled: Gender relations and working conditions of organic banana workers in the Huangalá and San Vicente de Piedra Rodada townships, Sullana - Piura, 2010-2012.